Electronic Effect on Catalytic Water Oxidation by Single Site [Ru(QCl–tpy)(bpy)(OH2)]2+ Catalyst. Issue 1 (9th January 2017) - Patel, Jully; Majee, Karunamay; Ahmad, Ejaz; Vatsa, Aditi; Das, Babulal; Padhi, Sumanta Kumar
Abstract: The mononuclear [Ru(QCl‐tpy)(bpy)(H2 O)](PF6 )2 was successfully synthesized and characterized by using several spectroscopic techniques (QCl‐tpy=2‐4′‐(2‐chloroquinolin‐3‐yl)‐2, 2′:6′, 2′′‐terpyridine). This complex shows only one pKa value at 10.2, due to the deprotonation from the bonded aqua ligand. This complex was successfully employed as a catalyst for chemical water oxidation in CF3 SO3 H solution (pH 1.0) by using Ce IV as an oxidant, shows initial turnover frequency (TOF) of 0.0014 s −1 . The manometry and electrochemical data shows that this complex is a better catalyst having turnover number (TON) 19 (out of 25) and overpotential of 600 mV. As compared to the parent Ru(tpy)(bpy)(H2 O)](PF6 )2 a higher catalytic effect was observed by complex1, which is expected due to the cause of electronic effect dominating towards electron donating behavior. Abstract : A mononuclear ruthenium complex having a single site for catalytic water oxidation has been synthesized and characterized thoroughly by various spectroscopic methods. The pKa of Ru II −OH2 Ru II −OH was observed at 10.2. The catalytic O2 evolution indicates that the rate is first order with respect to both catalyst and CAN. The electronic effects suggests the possibility of electron donating ability.